Marl clay bacteria in Mosul City, Iraq - R. A. K. Aswad; H. A. I. Al-Taii (Regulatory Mechanisms in Biosystems, 2025)
Marl is a mineral clay that residents of Mosul City use as a geophagic, food, medicine, and cosmetic ingredient. The interaction of clay minerals with microorganisms is common worldwide and holds significant environmental and economic importance. This study aims to investigate and evaluate microbial diversity present in m arl clays to determine how far this marl clay may serve as a potential source of bacterial isolates with valuable applications in medicine , industry and bioremediation , also to gather essential information on the safety of consuming these clays as food , medicine and cosmetics , and to address the lack of research in this area. Thirty m arl samples were collected and analyzed using X-ray diffraction (XRD) , show ing that the m arl clay was characterized by a unique mineral composition , mainly contain ing clay minerals: k aolinite, m ontmorillonite, p alygorskite, q uartz, and high content of c alcite, while some m arl samples contain ed d olomite and c hlorite. The results revealed that the pH was neutral. The study ultimat e ly resulted in the isolation and identification of bacteria from m arl clay in Mosul City through molecular methods, specifically 16S rRNA sequencing. Numerous bacterial isolates were identified including Actinobacteria, Betaproteobacteria, Firmic u t e s and Ga m maproteobacteria . Neither pathogenic bacteria not and Enterobacteriaceae were detected . The evolutionary relationships were d e termined using advanced software tools MEGA11 and iTOL v6.